2015
DOI: 10.1021/acs.inorgchem.5b00568
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Luminescence of Tenebrescent Na8Al6Si6O24(Cl,S)2: Multifunctional Optical Markers

Abstract: Na8Al6Si6O24(Cl,S)2 materials were prepared with a solid state reaction. The products were studied using X-ray powder diffraction, reflectance measurements as well as X-ray fluorescence, conventional and persistent luminescence, nuclear magnetic resonance, and electron paramagnetic resonance spectroscopies. All materials containing sulfur showed purple tenebrescence, which persisted 2 days in a lit room at room temperature. Considerable blue persistent luminescence peaking at 460 nm and lasting for 1 h was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 26 publications
6
47
0
Order By: Relevance
“…To put it simply, all the curves cover broad bands in the temperature range from 300 to 500 K. Furthermore, the TL intensity is closely related to the doping concentration of Eu 2+ ions, indicating that Eu 2+ ions has an influence on the trap depth and distribution. 37 The 3D TL spectra of LSA:0.02Eu 2+ monitored at different temperature and wavelength are presented in Figure 5A. The profile shapes of all the curves are consistent with each other and the PersL characteristics of TL mostly originate from the 5d-4f transitions of Eu 2+ ions with a maximum peaking at 518 nm.…”
Section: Thermoluminescence Propertiessupporting
confidence: 61%
See 2 more Smart Citations
“…To put it simply, all the curves cover broad bands in the temperature range from 300 to 500 K. Furthermore, the TL intensity is closely related to the doping concentration of Eu 2+ ions, indicating that Eu 2+ ions has an influence on the trap depth and distribution. 37 The 3D TL spectra of LSA:0.02Eu 2+ monitored at different temperature and wavelength are presented in Figure 5A. The profile shapes of all the curves are consistent with each other and the PersL characteristics of TL mostly originate from the 5d-4f transitions of Eu 2+ ions with a maximum peaking at 518 nm.…”
Section: Thermoluminescence Propertiessupporting
confidence: 61%
“…The decay and fitting curves of typical LSA: x Eu 2+ are presented in Figure C. It is evident that the measured results in the early stage is well‐fitted into biexponential function as follows:It=I0+A1exptτ1+A2exptτ2+A3exptτ3here, I (t) and I 0 are the PersL intensity at time t and 0, A 1 , A 2 , and A 3 are constants, t is time, and τ 1 , τ 2 , and τ 3 are the decay times. The fitting parameters are also listed in Table .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Yet, in this study the samples with the strongest tenebrescence are not the samples with the highest S content, but actually show concentrations around or below the detection limit. Also Norrbo et al (2015) found stronger tenebrescence for samples with low (n(S):n(Cl) = 0.06) and weak tenebrescence with increasing S concentrations, even though the mechanism behind could not be fully solved. This is in contrast to, e.g.…”
Section: Tenebrescencementioning
confidence: 89%
“…Yet, we found another mechanism that is influencing the unit cell and that is S. Figure 8 shows a close to linear increase in unit-cell size with increasing S content. Norrbo et al (2015) observed Cell constant a of samples plotted against PL (subgrouped into LW-and SW-UV) and tenebrescence. No systematics can be observed for PL (neither LW nor SW).…”
Section: Cell Constant a (å)mentioning
confidence: 95%